Resignification of Educational E-innovation to Enhance Opportunities for Graduate Employability in the Context of New University Degrees - Rosa María Torres Valdés; Alba Santa Soriano; Carolina Lorenzo Álvarez (Springer, 2018)
This paper presents the findings of a training programme based on an Action-Research methodology that has been applied in two subjects of Event Organization, Protocol and Institutional Relations undergraduate and Master's degrees. Through a teaching methodology called «learning by doing», students are encouraged to understand, internalise and apply the potential of technology in this field of knowledge, by means of building their personal brand as a key for digital literacy and professional empowerment. Thus, firstly this work proposes a review of the use of technology in teaching, with the goal of resignifying the concept of educational e-innovation from a transdisciplinary approach, which promotes progress in education ranging from technological to social innovation (technological-education-cultural-relational). Then, both the specific features and activities designed to build the students' personal brands during the course as well as the research methodology applied to analyze the results are described. The methodology is based on a longitudinal «ex post-facto» approach through a panel sample survey. Finally, results demonstrate how this training programme has allowed graduates to improve their employability and career development opportunities from then on, encouraging active participation and self-directed learning. Initial conclusions encourage us to apply this experience to larger groups and new university degrees in the higher education context.